2019
DOI: 10.34302/2019.11.4.13
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Antidiabetic and Anticholesterol Properties of Biscuit Product With Mangrove Fruit Flour (Mff) Substitution

Abstract: These fruits contain bioactive compounds and dietary fibers which is very potential for substitution to biscuit products. This study evaluated the antidiabetic and anticholesterol properties in the produced biscuits that were substituted with mangrove fruit flour (Pedada and Lindur fruits). This study used split plot design consisted of 2 factors. The first factor was divided into 5 groups (positive control group, negative control group, biscuit control group, Pedada biscuit group, and Lindur biscuit group), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Previous research has shown that mangrove flour type Bruguiera gymnorrhiza can reduce lipid profiles in rats. Fiber content and antioxidants in the form of saponins, flavonoids, and tannins are thought to cause a decrease in lipid profiles (Jariyah et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Previous research has shown that mangrove flour type Bruguiera gymnorrhiza can reduce lipid profiles in rats. Fiber content and antioxidants in the form of saponins, flavonoids, and tannins are thought to cause a decrease in lipid profiles (Jariyah et al, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…This study consisted of three stages, including (1) the creation of mangrove fruit flour (pedada and lindur), porang flour and mocaf, (2) production of ten flake formulation, with a mangrove flour and porang flour to mocaf ratio of 0: 100, 10:90 and 20:80 (see Table 1), (3) This involves determining the respective glycemic index. This study was approved by ethics commission no.…”
Section: Methodsmentioning
confidence: 99%
“…Besides, mangrove fruit flours (MFFs), including the pedada fruit flour (PFF) and lindur fruit flour (LFF) varieties are made from fruits of the mangrove species pedada (Sonneratia caseolaris) and lindur (Bruguiera gymnorrhiza). Previous studies on both flour types have shown possible application as substitutes in biscuit products, with anti-diabetic and anti-cholesterol properties [3], [4]. However, flakes have the advantage of being light, popular and widely consumed by the public.…”
Section: Introductionmentioning
confidence: 99%